Influence of Saltwater Submergence on Geohydraulic Properties of Sand: A Laboratory Investigation - Sudip Basack; Ghritartha Goswami; Sumanpran Sonowal; Moses Karakouzian (Hydrology, 2021)
Saline water intrusion into freshwater aquifers is a major geohydraulic problem relevant to coastal environment. Apart from contaminating the fresh groundwater resources, the saltwater intrusion alters the geotechnical properties of the aquifer materials, affecting the coastal water resource planning and management. The present study focuses on an in-depth laboratory investigation of the influence of saltwater submergence on the geohydraulic properties of sand. The fine sand sample was submerged under saline water of specified concentrations for specific periods, and the alteration in their engineering properties has been studied. It is observed that the specific gravity, dry density, and permeability of fine sand is significantly affected by the period of submergence and saline concentration. The specific gravity of sand particles was observed to increase almost linearly with period of submergence and saline concentration. While the sand dry density decreased fairly linearly with the period of submergence, the same is not being affected significantly by saline concentration. The permeability of sand increased nonlinearly with both period of submergence and saline concentration; for a submergence period of 14 days and saline concentration of 30,000 ppm, the permeability increased to a maximum value.